2015
DOI: 10.1371/journal.pone.0129761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AcHERV-GmCSF as an Influenza Virus Vaccine Adjuvant

Abstract: IntroductionThe first identification of swine-originated influenza A/CA/04/2009 (pH1N1) as the cause of an outbreak of human influenza accelerated efforts to develop vaccines to prevent and control influenza viruses. The current norm in many countries is to prepare influenza vaccines using cell-based or egg-based killed vaccines, but it is difficult to elicit a sufficient immune response using this approach. To improve immune responses, researchers have examined the use of cytokines as vaccine adjuvants, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Previously, we applied the HPV and influenza vaccine using the AcHERV system. 5,6 We confirmed that the immune response continues to increase after 3 times vaccination with AcHERV system. The increase in immune responses to HPV or influenza suggests that vaccination using the AcHERV system has no problems in gene delivery because of the low immune response to endogenous retroviral envelope proteins in mice.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Previously, we applied the HPV and influenza vaccine using the AcHERV system. 5,6 We confirmed that the immune response continues to increase after 3 times vaccination with AcHERV system. The increase in immune responses to HPV or influenza suggests that vaccination using the AcHERV system has no problems in gene delivery because of the low immune response to endogenous retroviral envelope proteins in mice.…”
Section: Discussionsupporting
confidence: 69%
“…Previously, we reported the immunization efficacy of influenza DNA vaccines based on a HERV-coated baculoviral DNA vaccine system for human use. 5,21 In this study, we successfully constructed a PERVenveloped baculovirus delivery system for porcine use. Compare to full length of PERV env, signal sequence and transmembrane modified PERV env showed more efficient delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, blood samples were collected from mice and sera were obtained. Ninety-six well plates were coated overnight with 8 hemagglutination units (HAU) of inactivated pH1N1 using standard methods, as previously described [ 30 , 31 ]. The absorbance at 450 nm (A450) was measured using an ELISA plate reader (Bio-Rad, Hercules, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Choi et al reported that female mice immunized with an inactivated influenza vaccine together with a murine granulocyte-macrophage colony-stimulating factor (GmCSF) gene delivered by the AcHERV system showed stronger humoural and cellular immune responses than mice immunized with the inactivated vaccine alone.Influenza-GmCSF-vaccinated mice were fully protected from lethal influenza virus challenge. 77 These findings showed that HERVs exhibit multiple functions in vaccine design. Recently, Segel et al identified one LTR retrotransposon homolog, paternally expressed gene 10 (PEG10) that preferentially bound and facilitated vesicular secretion of messenger RNA (mRNA).…”
Section: Therapies Utilizing Herv Toolsmentioning
confidence: 96%